2019
DOI: 10.5964/ejop.v15i1.1695
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy mentality in post-conflict societies: Relations with the ethos of conflict and readiness for reconciliation

Abstract: After almost 20 years since the end of the armed conflicts in former Yugoslavia, we are witnesses to the fact that the main causes of the conflicts have not been overcome. Reconciliation between ethnic groups that had been in conflict by means of economic and political cooperation, must have a psychological foundation. This study investigates the relations between Conspiracy Mentality, basic lexical social attitudes, and the factors important for Croatian-Serbian and Kosovo Albanian-Serbian reconciliation, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Specifically, two papers explored the consequences of conspiracy beliefs on important societal outcomes, while one paper investigated the inherent structure of conspiratorial beliefs. A study by Petrović, Međedović, Radović, and Radetić Lovrić (2019, this issue) shed new light on the psychological roots of unwillingness to reconcile. In addition to Ethos of Conflict (Bar-Tal, 2007) and basic social attitudes (Saucier, 2013), which are already found to be important ingredients in unwillingness to reconcile, the authors introduce the Conspiracy Mentality, i.e.…”
mentioning
confidence: 99%
“…Specifically, two papers explored the consequences of conspiracy beliefs on important societal outcomes, while one paper investigated the inherent structure of conspiratorial beliefs. A study by Petrović, Međedović, Radović, and Radetić Lovrić (2019, this issue) shed new light on the psychological roots of unwillingness to reconcile. In addition to Ethos of Conflict (Bar-Tal, 2007) and basic social attitudes (Saucier, 2013), which are already found to be important ingredients in unwillingness to reconcile, the authors introduce the Conspiracy Mentality, i.e.…”
mentioning
confidence: 99%
“…However, there is some data suggesting that the concept is applicable to other conflict situations, for example the ethnic conflicts in former Yugoslavia. The existing empirical findings showed that EOC (societal beliefs regarding the conflict between Serbs and Albanians on Kosovo) is positively related to the endorsement of conservative political parties (Međedović & Petrović, 2013), thinking pattern which is characteristic for militant and violent extremists (Međedović & Petrović, 2016), and the endorsement of conspiracy theories, while it showed negative associations with readiness to reconciliation (Petrović, Međedović, Radović, & Lovrić, 2019). These findings suggest that the socio-psychological aspects of violent conflict might be similar in various conflicts which originated in diverse cultures.…”
Section: The Ethos Of Conflictmentioning
confidence: 91%
“…While we are unaware of studies linking a conspiracy mentality to citizens' acceptance of violenceinducing rumors, previous studies have found citizens prone to believe in conspiracies to be more likely to endorse violence (Imhoff, Dieterle, and Lamberty 2020; Jolley and Paterson 2020) and to be less like to endorse reconciliation in post-conflict societies (Petrović et al 2019).…”
Section: Appeals To Government Distrust and The Spread Of Rumorsmentioning
confidence: 95%